Application of Diversified Health Education Combined with Psychological Nursing in the Treatment of Patients with Infectious Bone Defects by Induction Membrane Surgery - Ni Wang; Ling Wei; Rui Xiong; Dong Cheng (Emergency Medicine International)
Objective. To explore the application value of diversified health education combined with psychological nursing in the treatment of patients with infectious bone defects by induction membrane surgery. Methods. A total of 52 patients with infectious bone defects treated by induction membrane surgery from May 2018 to January 2022 were selected as the research subjects and divided into an observation group (with diversified health education combined with psychological care) and a control group according to the random number table method (routine nursing care). There were 26 patients in each group, and the Hospital Anxiety and Depression Scale (HADS) and Self-Care Ability Scale (ESCA) were compared. Results. At admission, there was no significant difference in anxiety dimension, depression dimension, and total score of anxiety and depression between the two groups (P>0.05). At admission, there was no significant difference in self-care responsibility, self-concept, self-care skills, health knowledge level, and total score between the two groups (P>0.05). Skills, health knowledge level, and total score were higher than those in the control group (P<0.05). The total incidence of complications in the observation group was lower than that in the control group (P<0.05). Conclusion. Diversified health education combined with psychological nursing is beneficial to reduce negative emotions, improve self-care ability, and reduce the incidence of complications in the treatment of patients with infectious bone defects by induction membrane surgery.